2008
DOI: 10.1080/07315724.2008.10719722
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Concentrated Barley β-Glucan in Mildly Hypercholesterolemic Adults

Abstract: Overall, supplementation with isolated barley beta-glucans of different molecular weights had small effects on cardiovascular disease markers. Molecular weight of the barley fiber did alter effects on body weight with the high-MW fiber significantly decreasing body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…Mnohé studie prokazují (Keogh et al, 2003;Chen a Raymond, 2008;Shimizu et al, 2008;Smith et al, 2008;Babio et al, 2010;Mitsou et al, 2010;Samuelsen et al, 2011;El Khoury et al, 2012;Tovar et al, 2012), že beta-glukany (podobně jako arabinoxylany) v lidské stravě pomáhají snižovat hladinu LDL cholesterolu a hladinu glukosy v krvi, inzulinovou odezvu po jídle, tělesnou hmotnost, krevní tlak, riziko srdeční choroby i rakoviny tlustého střeva a zároveň zmírňují průběh diabetu II. typu.…”
Section: Sladovnicky a Dieteticky Významné Neškrobové Polysacharidy Zunclassified
See 1 more Smart Citation
“…Mnohé studie prokazují (Keogh et al, 2003;Chen a Raymond, 2008;Shimizu et al, 2008;Smith et al, 2008;Babio et al, 2010;Mitsou et al, 2010;Samuelsen et al, 2011;El Khoury et al, 2012;Tovar et al, 2012), že beta-glukany (podobně jako arabinoxylany) v lidské stravě pomáhají snižovat hladinu LDL cholesterolu a hladinu glukosy v krvi, inzulinovou odezvu po jídle, tělesnou hmotnost, krevní tlak, riziko srdeční choroby i rakoviny tlustého střeva a zároveň zmírňují průběh diabetu II. typu.…”
Section: Sladovnicky a Dieteticky Významné Neškrobové Polysacharidy Zunclassified
“…There are many studies (Keogh et al, 2003;Chen and Raymond, 2008;Shimizu et al, 2008;Smith et al, 2008;Babio et al, 2010;Mitsou et al, 2010;Samuelsen et al, 2011;El Khoury et al, 2012;Tovar et al, 2012) proving that beta-glucans (similarly as arabinoxylans) in human diet help lower LDL cholesterol and glucose level in blood, insulin response to meal, body weight, blood pressure, risk of heart diseases and colon cancer and simultaneously they alleviate the course of type II diabetes. As a prebioticum, they stimulate in the colon the growth of bacteria producing volatile fatty acids, which create an unsuitable environment for the growth of pathogenic bacterial species, at the same time they act as nutrients for intestinal enterocytes.…”
Section: Sladovnicky a Dieteticky Významné Neškrobové Polysacharidy Zmentioning
confidence: 99%
“…Four randomised controlled trials were identified that presented evidence on β-glucan in relation to fasting insulin concentration, all of which were included in a meta-analysis (Saltzman et al, 2001;Chen et al, 2006;Maki et al, 2007a;Smith et al, 2008). Two trials were subsequently identified in the update search (Bays et al, 2011;Charlton et al, 2012) (Cardio-metabolic review, diabetes and glycaemia chapter p 311-312; Update search table 161).…”
Section: Fasting Insulinmentioning
confidence: 99%
“…Oat bran and β-glucans and fasting triacylglycerol concentration  Effect  Moderate evidence  The direction of the effect demonstrates higher consumption higher consumption of oat bran or β-glucan supplementation is beneficial to health  The effect is biologically relevant Fasting blood glucose 8.87. Four randomised controlled trials were identified that presented evidence on oat bran and β-glucan supplements in relation to fasting blood glucose concentration, all of which were included in a meta-analysis (Saltzman et al, 2001;Chen et al, 2006;Maki et al, 2007a;Smith et al, 2008). Two trials were subsequently identified in the update search (Bays et al, 2011;Charlton et al, 2012) (Cardio-metabolic review, diabetes and glycaemia chapter p 308-310; Update search table 155).…”
mentioning
confidence: 99%
“…single arm interventions without a control (placebo) group (Dongowski et al, 2006;Ikegami et al, 1996;Smith et al, 2008). One acute trial (Bourdon et al, 1999) measured postprandial plasma lipids after the intake of test meals.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%